Quantitative determination of periplocymarin in rat plasma and tissue by LC‐MS/MS: application to pharmacokinetic and tissue distribution study. (15th January 2016) - Yan, Kaijing; Wang, Xiangyang; Jia, Yumeng; Chu, Yang; Guan, Xiufeng; Ma, Xiaohui; Li, Wei; Pan, Guixiang; Zhou, Shuiping; Sun, He; Liu, Changxiao
Abstract: A simple, rapid and sensitive liquid chromatography with tandem mass spectrometry (LC‐MS/MS) method for the determination of periplocymarin in biological samples was developed and successfully applied to the pharmacokinetic and tissue distribution study of periplocymarin after oral administration of periplocin. Biological samples were processed with ethyl acetate by liquid–liquid extraction, and diazepam was used as the internal standard. Periplocymarin was analyzed on a C18 column with isocratic eluted mobile phase composed of methanol and water (containing 0.1% formic acid) at a flow rate of 0.2 mL/min (73:27, v/v). Detection was performed on a triple‐quadrupole tandem mass spectrometer using positive‐ion mode electrospray ionization in the selected reaction monitoring mode. The MS/MS ion transitions monitored were m / z 535.3→355.1 and 285.1→193.0 for periplocymarin and diazepam, respectively. Good linearity was observed over the concentration ranges. The lower limit of quantification was 0.5 ng/mL in plasma and tested tissues. The intra‐and inter‐day precisions (relative standard deviation) were <10.2 and 10.5%, respectively, and accuracies (relative error) were between −6.8 and 8.9%. Recoveries in plasma and tissue were >90%. The validated method was successfully applied to the pharmacokinetic and tissue distribution studies of periplocymarin in rats. Copyright © 2016 John Wiley & Sons, Ltd.